Coupled Design of Non-flow Ripple and Non-axial Force for Lightweight Roots Pump - Weifeng Wu; Jie Tong; Yulong Li (Jixie chuandong)
In order to realize non-flow ripple and non-axial force of roots pump with helical rotor and greater capacity utilization and smaller internal leakage as desired by its lightweight，for high cross shape coefficient of rotor，a construction method for chord height line of pitch arc of half lobe as internal conjugate profile segment and top profile segment with radial equal arc gap is proposed，from coupled relation without axial force between volume pair with helical rotor and power pair with helical gear，its coupled design method with non-axial force is derived and an example is given. All results show that plane-convex conjugate gap and top equal arc gap can effectively restrain conjugate leakage and radial leakage，and cause larger shape coefficient of 1.6 and larger volume utilization coefficient of 0.58 to come true，helical angle of 60° can realize theoretical non-flow ripple，and coaxial design with equal cross pitch radius of helical rotor and standard helical gear can be derived from helical angle of 20°~25°，and the coaxial design method is simple，etc. It provides a theoretical basis for future high quality development of roots pump.